An Atypical Presentation of Amoebic Liver Abscess: A Case Report - Gideon, Adolf; Saputra, I Wayan Eka; Adiputra, Pande Made Gunawan (Syntax Literate, 2025)
A 41-year-old male presented to the ER with a history of intermittent low-grade fever since 1 month ago, accompanied by epigastric pain and nausea for the past week. Abdominal ultrasonography revealed a 7,9 x 8.9 cm hyphoechoic lesion in the right lobe of liver, suggestive of a liver abscess. Upon further exam, the abdominal computed tomography (CT) scan confirmed a 8,4 x 8,9 cm liver abscess in the right lobe accompanied by ascites and pleuropneumonia. The diagnosis of amoebic liver abscess was established. The patient underwent intravenous antibiotic therapy followed by laparotomy drainage of the abscess. Following treatment, patient showed improvement and was discharged. This case report highlights the importance of thorough history-taking in suspected cases of liver abscess and differential diagnosis of liver abscess. Early recognition and appropriate management, including antibiotic therapy and surgical drainage when indicated, are crucial in achieving favorable outcomes for the patients. Keywords:,,,